Formation of a project culture among future managers of the sports industry in vocational education - Frolko M.S. ,; Levchenkova T.V. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to develop a project culture for future managers of the sports industry based on the application of the project method in professional education. Methods and structure of the study. The project culture of future managers of the sports industry is considered as a set of cognitive, value, activity, reflective and motivational components, which have their own levels of development, achieved in the process of students implementing project activities. A pedagogical experiment was carried out with students of the 2021 intake of the training direction 38.03.02 “Management” in the period from February 2023 to October 2023. The students were given the following tasks: creating a short-term individual mini-project within the framework of the educational special discipline “Marketing” and active participation in group projects of extracurricular activities. Using a specially designed questionnaire, research participants were surveyed before and after the experiment to assess the level of development of the components of the project culture. Results and conclusions. Analysis of the data obtained from a survey of sports industry managers showed that the use of the project method in the learning process provides positive dynamics, since according to all criterion indicators, the components of the project culture have increased. It is shown that the project method of teaching can become a key element in the formation of a project culture among future managers of the sports industry, providing students with the development of the necessary skills, knowledge, and personal qualities for a successful professional career.